2014
DOI: 10.1007/s00246-014-1057-5
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Pediatric Patients Undergoing Cardiac Catheterization While on Extracorporeal Membrane Oxygenation

Abstract: The aim of the study is to explore the indications for cardiac catheterization while on extracorporeal membrane oxygenation (ECMO) and the various catheter interventions performed as well as assess the safety profile and determine the short- and intermediate-term survival. ECMO is a lifesaving intervention for pediatric patients with respiratory and/or cardiovascular failure. There is limited recent literature discussing the survival and outcomes of patients undergoing cardiac catheterization while on ECMO. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 32 publications
2
35
1
Order By: Relevance
“…These findings provide evidence that early detection and treatment of unsuspected residual lesions reduces ECLS duration and improves outcome. The diagnostic utility of echocardiography in post‐operative pediatric cardiac patients on ECLS has been called into question, as echocardiography has failed to detect 40–52% of lesions discovered at catheterization in previous studies . Our findings are in line with these data, as echocardiography failed to detect 39.6% of lesions found during catheterization in this series.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…These findings provide evidence that early detection and treatment of unsuspected residual lesions reduces ECLS duration and improves outcome. The diagnostic utility of echocardiography in post‐operative pediatric cardiac patients on ECLS has been called into question, as echocardiography has failed to detect 40–52% of lesions discovered at catheterization in previous studies . Our findings are in line with these data, as echocardiography failed to detect 39.6% of lesions found during catheterization in this series.…”
Section: Discussionsupporting
confidence: 85%
“…In a retrospective review of 36 pediatric cardiac patients, those receiving a catheterization on ECLS day 0 or day 1 had significantly shorter ECLS durations than patients receiving a catheterization 2 or more days after initiation of support (4 days vs. 7 days, P ¼ 0.0008). 3 However, no difference in survival was seen between groups. Another retrospective review of 75 catheterizations in pediatric ECLS patients found that the mean ECMO-to-catheterization time was shorter in survivors than non-survivors (1.6 vs. 3.5 days).…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations